Działalność naukowa Stanisława Rosponda na Śląsku w latach 1945–1950 - Sochacka, Stanisława (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article presents a general characteristic of Stanisław Rospond’s academic and organizational activity in Silesia in the first years after World War II. This Polish and Slavic linguist, born near Cracow, a graduate of the Jagiellonian University, fascinated by the history of Silesia, moved to Wrocław in 1945.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne